The Correlation of Self-Efficacy and Emotional Intelligence with Learning Interest among Elementary School Students - Muhammad Noor; Pranciska Gamilina (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2026)
This study is motivated by the limited research on the simultaneous influence of self-efficacy and emotional intelligence on elementary students’ learning interest, despite their significant impact on academic engagement and holistic development. The study aims to examine the partial and simultaneous relationships between self-efficacy, emotional intelligence, and learning interest among upper-grade elementary students. Adopting a quantitative correlational design, the research involved a total sample of 63 students from Grades IV–VI selected through total sampling. Data were collected using Likert-scale questionnaires and analyzed using correlation, multiple regression, and first-order partial correlation techniques. The findings reveal significant positive relationships between self-efficacy and learning interest (r = 0.573, p < 0.05) and between emotional intelligence and learning interest (r = 0.565, p < 0.05), with both variables jointly explaining 39.6% of the variance in learning interest. These results indicate that self-efficacy and emotional intelligence play a synergistic role in fostering students’ learning interest. The implications encompass theoretical contributions to understanding cognitive and emotional determinants of student engagement and practical recommendations for teachers, schools, and parents to strengthen students’ self-confidence and emotional competencies. Future research is recommended to broaden sample diversity, include additional influencing factors, and employ longitudinal or mixed-method approaches to further elucidate the mechanisms shaping learning interest.